The relationship between job satisfaction and job motivation to the job performance among employees at Pejabat Pendidikan Daerah Kota Tinggi, Johor / Nor Farhana A. Zabil - A. Zabil, Nor Farhana (2014)
This study was done to explain the relationship between job satisfaction and job motivation with job performance among employees at Pejabat Pendidikan Daerah Kota Tinggi, Johor. The population of respondents for this study is 75 employees and the sample size is 63 respondents from Pejabat Pendidikan Daerah Kota Tinggi which are 84% from the total population. For the purpose of data collection, a questionnaire was used as the mam instruments. The questionnaire consists of four sections including demographic data, job motivation, job satisfaction, and job performance which then all items in the questionnaire were constructed according to research objectives and research questions. The data that we get from the questionnaires were analyzed by using the SPSS version 20.0 that involved the use of frequency distribution and correlation test. Based on the result showed, all the independent variables and dependent variable have significant relationship even though there is weak. Therefore, it can be concluded that job satisfaction and job motivation can influence the job performance among employees at Pejabat Pendidikan Daerah Kota Tinggi, Johor.